Les Navajo en transition : la difficile maîtrise d’un nouvel espace-temps - Gérard Selbach (Revue LISA)
What happens when a society like that of the Navajo is faced with a Euro-American concept of space and time exerting tension and pressure on its way of thinking, its beliefs and its traditional way of life? The Navajo tetragram made of spirituality, limited space (the land of their ancestors) and present time (continuity) is faced with another: secularity, unlimited space and just-in-time, typical of the free-market and consumer society. These are two cultures, two sets of values that seem irreconcilable except for the Navajo who, thanks to Hózhó, live an ambivalent balance: “We are two in one.”